Domain binding and isotype dictate the activity of anti-human OX40 antibodies - C Ian Mockridge; Kerry L Cox; Martin J Glennie; Mark S Cragg; Monika Semmrich; Linda Mårtensson; Ingrid Teige; Jordana Griffiths; Khiyam Hussain; Hannah L Smith; Theodore Sanders; Jinny Kim; et al. (Journal for ImmunoTherapy of Cancer)
Background Previous data suggests that anti-OX40 mAb can elicit anti-tumor effects in mice through deletion of Tregs. However, OX40 also has powerful costimulatory effects on T cells which could evoke therapeutic responses. Human trials with anti-OX40 antibodies have shown that these entities are well tolerated but to date have delivered disappointing clinical responses, indicating that the rules for the optimal use of anti-human OX40 (hOX40) antibodies is not yet fully understood. Changes to timing and dosages may lead to improved outcomes; however, here we focus on addressing the role of agonism versus depleting activity in determining therapeutic outcomes. We investigated a novel panel of anti-hOX40 mAb to understand how these reagents and mechanisms may be optimized for therapeutic benefit.Methods This study examines the binding activity and in vitro activity of a panel of anti-hOX40 antibodies. They were further evaluated in several in vivo models to address how isotype and epitope determine mechanism of action and efficacy of anti-hOX40 mAb.Results Binding analysis revealed the antibodies to be high affinity, with epitopes spanning all four cysteine-rich domains of the OX40 extracellular domain. In vivo analysis showed that their activities relate directly to two key properties: (1) isotype—with mIgG1 mAb evoking receptor agonism and CD8+ T-cell expansion and mIgG2a mAb evoking deletion of Treg and (2) epitope—with membrane-proximal mAb delivering more powerful agonism. Intriguingly, both isotypes acted therapeutically in tumor models by engaging these different mechanisms.Conclusion These findings highlight the significant impact of isotype and epitope on the modulation of anti-hOX40 mAb therapy, and indicate that CD8+ T-cell expansion or Treg depletion might be preferred according to the composition of different tumors. As many of the current clinical trials using OX40 antibodies are now using combination therapies, this understanding of how to manipulate therapeutic activity will be vital in directing new combinations that are more likely to improve efficacy and clinical outcomes.